Colchicine in Patients with Acute Ischemic Stroke: A Meta-Analysis of Randomized Trials - Joshuan J. Barboza; Oriana Rivera-Lozada; César Bonilla-Asalde; Luis G. Chancha-Martínez; Víctor A. Mañuico-Antay; Alexis Ccoyllo-Mayhuasca; Luis E. Balcázar-Rincón; Dante Raúl Torres-Huamaní; Briseidy Ortiz-Rodríguez; Mahycol Bravo-Ramirez (Journal of Clinical Medicine, 2026)
Background: Inflammation plays a key role in atherosclerosis and thromboinflammatory processes involved in ischemic stroke. Colchicine, an anti-inflammatory agent that inhibits microtubule polymerization and inflammasome activation, has demonstrated cardiovascular benefits in coronary artery disease. However, its effectiveness in secondary prevention after ischemic stroke remains uncertain. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating colchicine in two pre-specified populations: (i) patients with non-cardioembolic ischemic stroke or high-risk transient ischemic attack (TIA), and (ii) atherosclerotic cardiovascular disease (ASCVD) cohorts reporting cerebrovascular outcomes, with pre-planned subgroup and sensitivity analyses restricted to stroke/TIA-only trials to address indirectness. Methods: We searched PubMed, Scopus, Web of Science, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception to 20 October 2025, with no language restrictions, using a fully reported strategy combining controlled vocabulary (MeSH/Emtree) and free-text terms for colchicine and cerebrovascular/atherosclerotic outcomes. The primary outcome was recurrent stroke. Secondary outcomes included composite major vascular events, serious adverse events, any adverse events, and treatment discontinuation due to adverse events. A pre-specified subgroup analysis compared stroke/TIA-dedicated trials versus ASCVD trials reporting cerebrovascular outcomes, and a sensitivity analysis was restricted to stroke/TIA-only trials. Random-effects meta-analysis was performed using risk ratios (RR) with 95% confidence intervals (CI). Heterogeneity was assessed using the I2 statistic, and the certainty of evidence was evaluated using the GRADE framework. Results: Five randomized controlled trials, including 18,336 participants, were included. Colchicine did not significantly reduce the risk of recurrent stroke compared with control therapy (RR 0.86, 95% CI 0.65–1.12). Similarly, no significant reduction in vascular events was observed (RR 0.70, 95% CI 0.40–1.23), with substantial heterogeneity across studies. Colchicine was not associated with a significant increase in serious adverse events (RR 1.14, 95% CI 0.43–2.97). When restricted to stroke/TIA-dedicated trials (CHANCE-3, CONVINCE, COPS), the point estimate for recurrent stroke remained close to the null. Across trials reporting tolerability, colchicine was associated with higher rates of gastrointestinal adverse events and study-drug discontinuation, although the magnitude varied across studies. According to GRADE, the certainty of evidence ranged from moderate for recurrent stroke to low for vascular events and serious adverse events. Conclusions: Colchicine did not significantly reduce recurrent stroke or vascular events in patients with ischemic stroke or transient ischemic attack. Current evidence does not support routine use of colchicine for secondary stroke prevention, and further randomized trials are needed to identify potential subgroups that may benefit from anti-inflammatory therapy.